Electromagnetic nonlinear parametric study of the SynRM using FEM method - Benessalah Djamel; Houassine Hamza; Nadir Kabache; Moussaoui Djeloul (Institute of Advanced Engineering and Science, 2021)
The interest in synchronous reluctance machine (SynRM) does not stop increasing in recent decades; this is encouraged by their numerous advantages. This paper presents a nonlinear parametric study of the SynRM using finite element method (FEM) method. After a brief introduction and a description of the basic principles of SynRM an investigation and an evaluation of the effects of some influential parameters’ variables of the machine on the torque and magnetic losses is highlighted. The SynRM is created using ANSYS Maxwell software, using 2D FEM. The analyses are performed in the ANSYS Maxwell. The influence of the thickness of the air gap, the opening angle of the rotor, the width and the height of the stator tooth are listed and discussed. The obtained results reveals that the opening angle of the rotor and the air gap produces a large effect over the torque of the SynRM. In order to validate, the finite element model of the studied machine, experimental tests were carried out on designed machine such as the measurement of the synchronous inductance, the torque and the different losses. The experimental results are in agreement with those obtained by FEM.